Predictors of severe disease in Streptococcus dysgalactiae subsp. equisimilis bacteremia: a population-based study - Miia Saukkosaari; Janne Aittoniemi; Reetta Huttunen; Tiina Luukkaala; Sari Rantala (BMC Infectious Diseases)
Abstract Background Streptococcus dysgalactiae subsp. equisimilis (SDSE) is a leading cause of invasive β-hemolytic streptococcal infections in many countries and is increasingly recognized as a cause of severe disease. However, clinical data on severe SDSE disease remain limited. The aim of this study was to identify predictors of severe disease in SDSE bacteremia. Methods This retrospective study covered 217 episodes of SDSE bacteremia in 211 adult patients in the Pirkanmaa area, Finland from August 2015 to June 2018. Severe disease was defined as admission to an intensive care unit (ICU) and/or death. Results 10% of the patients had severe disease, and the overall 30-day case-fatality rate was 7.8%. Alcohol abuse (odds ratio [OR] 5.5 [95% confidence interval (CI) 1.1–28], p = 0.038) and malignancy (OR 4.2 [1.3–13], p = 0.014) were significantly associated with severe disease. Unconsciousness (OR 23 [1.9–271], p = 0.018), dyspnea (OR 5.4 [1.7–17], p = 0.005) or falling (OR 3.8 [1.1–13], p = 0.031) as the first sign or symptom predicted severe disease. Conclusion Alcohol abuse, malignancy, as well as unconsciousness, dyspnea and falling as first signs of infection were associated with severe disease in SDSE bacteremia. These novel findings expand our knowledge of SDSE bacteremia and provide valuable insights for identifying patients at the highest risk of severe disease.